Pengalihan Harta Warisan Berdasarkan Kompilasi Hukum Islam - Indra Pratama; Nurasiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
In Islam, inheritance is regulated by provisions in the Quran to prevent disputes among heirs after the death of a person whose property is inherited. Islamic religion requires and establishes the principle of fairness and justice as one of the pillars of community formation and development that must be upheld. These provisions cannot be implemented properly and effectively without the support of experts who have a deep understanding and are able to implement these provisions properly. The purpose of this study is to determine and analyze the distribution of inheritance among dzawil arham heirs in accordance with the Compilation of Islamic Law (KHI) and to determine the validity of the decree of the village head of Suka Damai Timur Village. This study uses a qualitative research method with an exploratory and descriptive approach. This study involved the community as sources, namely the village head, religious leaders, heirs, and community and traditional leaders. Data collection was obtained through interviews as primary data, and secondary data was obtained through literature studies. The results of the study show that the validity of the village head's decree on the transfer of inheritance depends on several legal factors that must be fulfilled. The village head does not have the legal authority to issue an official decree that is legally binding in the transfer of inheritance. This authority legally rests with certain officials, such as notaries or land deed officials (PPAT) and the courts. The distribution of inheritance assets in the community of Suka Damai Timur Village regarding the transfer of inheritance assets to ahli dzawil arham (heirs) is carried out using a deliberative system with a bilateral and parental system. The validity of the village head's decree on the transfer of inheritance assets based on the Compilation of Islamic Law (KHI) generally requires that the transfer of inheritance assets comply with the applicable laws in Indonesia and meet the applicable administrative requirements. The validity of the village head's decree on the transfer of inheritance assets should be tested in a religious court.